1991
DOI: 10.1177/0013161x91027004004
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Absenteeism in Secondary Education

Abstract: Teacher absenteeism is a serious problem for school systems. Using an existing model of attendance behavior as a guide, attitudina~ demographic, and absenteeism data from 265 secondary teachers were examined. Canonica/ correlation analysis revealed that absenteeism among teachers was significantly related to distance to work, gender, job involvement, and overall job satisfaction.Absenteeism represents a costly problem for all organizations, but none more so than for elementary and secondary school systems. Lew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 40 publications
0
7
1
2
Order By: Relevance
“…Finally, it should also be pointed out that this study does not support the findings of Taylor (1981) who suggested that younger teachers tend to be more absent than older teachers, or Scott and Winbush (1991) who claimed that women tend to be more absent than men.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…Finally, it should also be pointed out that this study does not support the findings of Taylor (1981) who suggested that younger teachers tend to be more absent than older teachers, or Scott and Winbush (1991) who claimed that women tend to be more absent than men.…”
Section: Discussioncontrasting
confidence: 95%
“…Although several studies have supported the theory of a relationship between work attitude and voluntary absence (Pellicer, 1984;Scott & Winbush, 1991), a comprehensive review of the literature shows that only 'little variation in reported correlation between absence and satisfaction can be attributed to the type of absence measure used, whether voluntary or involuntary' (Hackett & Guion, 1985, p. 355). Similar results were achieved with regard to organizational commitment (Randall, 1990).…”
Section: Absence From Work: a Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned earlier, female teachers tend to be absent more often than male teachers. Researchers have also found a positive relationship between the distance that a teacher commutes to school and rate of absence (Beavers, 1981;Bridges & Hallinan, 1978;Educational Research Service, 1980;Scott & Wimbush, 1991;Winkler, 1980). A teacher's age has also been linked to rates of absence, though this relationship is not monotonic-the youngest and the oldest teachers tending to be absent more often than teachers of intermediate ages (Bradley et al, 2007;Educational Research Service, 1980).…”
Section: Why Are Some Teachers Absent More Often Than Other Teachers?mentioning
confidence: 99%
“…Interruptions in the continuity of the students' instruction contribute to lower achievement (Woods and Montagno, 1997). Concomitant problems of absenteeism are teacher resistance to change or input, negativity, and low motivation (Scott and Wimbush, 1991). Financially, teacher absence can easily translate into direct costs to school management.…”
Section: Introduction Rationale and Purposementioning
confidence: 99%